Perceived not actual overweight is associated with excessive school absenteeism among U.S. adolescents. Issue 4 (July 2017) - Duncan, Dustin T.; Hansen, Andrew R.; Woo Baidal, Jennifer; Lyn, Rodney; Hill, Ashley; Zhang, Jian
Highlights: Overweight was linked to absenteeism, the most disruptive situations in childhood. Which matters most, measured or perceived if mismatched, remain unclear. Perceived body image rather measured weight was associated with absenteeism. Normal weight teenagers who self-perceived as overweight were at a highest risk. Self-perceived image had a more profound psychiatric impact than measured weight. Summary: Background: Excess body weight has been reported to be associated with excessive school absenteeism (ESA), but less is known about the association with perceived body weight. The study objective was to weigh the relative influence of perceived and measured weight status on school attendance. Methods: We used the data from 3113 adolescents age 12–19 years who were interviewed as a part of the National Health and Nutrition Examination Surveys (NHANES), 2003–2008. Body weight and height were measured during the physical examination, while self-perceived body weight and the number of school days missed was assessed using questionnaires. Missing one or more days per school month (nine days per school year) was defined as, and indicative of, experiencing ESA. Results: ESA was reported from 12.31 (SE = 0.89) % of adolescents. The highest prevalence occurred among healthy weight adolescents who erroneously self-perceived as overweight [21.6 (4.77) %], two times higher than adolescents with obesity who self-perceived as "just right weight" [10.3 (2.87) %]. The adjusted prevalence ratio (PR) of ESA for healthy weight adolescents who erroneously self-perceived as "overweight" was 1.91 (95%CI = 1.10–3.32) compared to healthy weight peers who correctly self-perceived as "just right" (reference group). The PRs were 0.99 (0.48–2.06) and 1.41 (0.86–2.32) respectively for adolescents with obesity who believed that their body weight was "just right" or "overweight". No significant differences were observed between boys and girls, young (12–15 years) and older adolescents (16–19 years). Conclusions: Perceived overweight rather than actual overweight is significantly associated ESA among adolescents.